2013
DOI: 10.1002/ccd.24739
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of a traumatic ventricular septal defect using an amplatzer™ atrial septal occluder device

Abstract: A relatively rare occurrence, the incidence of ventricular septal defect (VSD) complicating penetrating cardiac trauma has been reported at 4.5%. Closing such defects may be challenging especially in an unstable patient where cardiopulmonary bypass may exponentially increase the surgical risk. In such patients, catheter-based device closure is a reliable and effective alternative. We describe case of a 30 year old man who presented with a stab wound to his anterior mediastinum. His injuries involved laceration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Хирургическое вмешательство необходимо в случае гемодинамически значимых повреждений. Наиболее часто вмешательство проводится по поводу дефектов мышечной части МЖП как традиционным открытым хирургическим способом с доступом к входному и выходному отверстиям раневого канала через различные камеры сердца или магистральные сосуды в условиях искусственного кровообращения [6,10,17,36,48,[50][51][52][53][54][55][56][57][58], так и посредством чрескожной транскатетерной имплантации современных окклюдеров [33,45,[59][60][61][62][63].…”
Section: Discussionunclassified
“…Хирургическое вмешательство необходимо в случае гемодинамически значимых повреждений. Наиболее часто вмешательство проводится по поводу дефектов мышечной части МЖП как традиционным открытым хирургическим способом с доступом к входному и выходному отверстиям раневого канала через различные камеры сердца или магистральные сосуды в условиях искусственного кровообращения [6,10,17,36,48,[50][51][52][53][54][55][56][57][58], так и посредством чрескожной транскатетерной имплантации современных окклюдеров [33,45,[59][60][61][62][63].…”
Section: Discussionunclassified
“…Afterwards, only three cases by Berry et al. [ 13 ] and Ali et al [ 17 ] , with good results (low postoperative recovery, total cardiac function restore without any interventricular septum shunt) were published. The use of minimally surgery (opening, controlling and treating the cause of bleeding) associated with the percutaneous occluder device implantation in penetrating cardiac injuries with iatrogenic VSD may be a complete and safe approach to this trauma patient.…”
Section: Discussionmentioning
confidence: 99%
“…5) A review of the literature shows that a few cases of traumatic VSD have thus far been managed with an ASO device. 4,[6][7][8][9] In our patient, we decided to use an ASO device because the initial 18 mm AmVSDO easily prolapsed through the defect and due to the unavailability of a larger AmVSDO. Our case showed that transcatheter closure with ASO appears to be an option for patients with a large post-traumatic muscular VSD and significant hemodynamic compromise.…”
Section: Discussionmentioning
confidence: 99%
“…In their report, they advise against using an ASO device for traumatic VSD closure. Ali, et al 7) recently also utilized a 24 mm ASO device to close a traumatic VSD and they also reported hemolysis as a complication that was resolved by conservative medical management. However, our case demonstrated intractable hemolysis that was managed with surgical device removal.…”
Section: Discussionmentioning
confidence: 99%